PELAKSANAAN PEMBERIAN KREDIT KEPADA USAHA MIKRO KECIL DAN MENEGAH OLEH BANK RAKYAT INDONESIA SYARIAH KOTA PEKANBARU - Hariyawati, Desi; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Understanding the Syariah principle contained in Article 1 paragraph 13 of Law No. 10 of 1998 which reads principle of Shariah is Islamic law based on the treaty rules between the bank and other parties to hold funds or financing business activities, or other activities stated in accordance with sharia. Understanding Micro by PB BI No. 14/22/PBI/2012 Article 1 paragraph 5 which reads Micro is a productive enterprise belonging to individuals and/or individual business entities, which meet the criteria of Micro, as stipulated in Law No. 20 of 2008 on UMKM. UMKM applying for loans to BRI Syariah must include assurances can be book Owners of Motor Vehicles, Land Certificate, or other securities. However, if the loan requested under Rp 25.000.000, the BRI Syariah establish UMKM do not have to include a guarantee. But in reality, there are UMKM that can not make loans under Rp 25.000.000.Issues examined in this study are: First, How is the implementation lending to micro, small and medium enterprises by BRI Syariah? Second, Is BRI Syariah considerations does not provide credit facilities to the Micro, Small and Medium Enterprises in the city of Pekanbaru?This type of research is a sociological research. Source data used are primary data and secondary data, engineering data collection using interviews and literature study.This study uses a qualitative analysis. By Using conclusion inductive method of thinking.The results of this study are the First, extension of credit to UMKM, BRI Syariah Pekanbaru perform field checks, checks of applications, BICheking data checks, check the surrounding environment, and did a survey of UMKM who submitted pinjaman.UMKM were applying for loans to BRI Syariah must include a guarantee in the form books Own Vehicle, Land Certificate, or other securities. If the loan is requested under Rp 25.000.000, the BRI Syariah establish UMKM do not have to include a guarantee. However, in practice there are UMKM that can not make loans under Rp 25.000.000, -Second, BRI Syariah Advisory Pekanbaru does not provide credit facilities to UMKM because of the absence of guarantees for loans below Rp 25,000,000, is not appropriate , because according to the rules that the Bank Shall provide loans under Rp 25.000.000, without using collateral. Consideration should be avoided not accept to run the obligation to provide credit support to UMKM.Keywords: PT. BRI Syariah Pekanbaru - UMKM - Credit